Implementation Of Mining Management And Enterprise Policies Based On The Principles Of Social Justice And Community Welfare - Eddy - Pelupessy (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research aims to find out and understand the management and exploitation policies of mining natural resources, as well as to know and understand the application of the concept of community-based justice in the management of mining natural resources. Using a socio-cultural juridical approach, that law cannot be separated from people's lives. Data collection techniques were carried out by means of interviews, distributing questionnaires and observation. The results of the research reveal that constitutionally the management and exploitation of mines based on community justice has been carried out in three ways, namely regulation, management and supervision. Mining industry practices in Bogobaida District, Noumowodide Village, Paniai Regency, found illegal gold mining practices carried out by mining companies and the community around the mining area itself, they did not apply the principles of gold mining work that were good and beneficial for future generations. Therefore, to maximize legal protection and apply the concept of local community-based justice in a number of mining areas, the Paniai Regency Government has issued Paniai Regent Decree Number 14 of 2014 concerning the termination of Unlicensed Gold Mining Activities (PETI) in the Bogobaida District, Noumowodide Village. Regency/City Regional Governments must be proactive in mapping mineral potential in their areas and must pay attention to licensing provisions regulated by government policies in the mining, mineral and coal sectors.